Curriculum, work readiness, and employability in Malaysian higher education : unpacking the nexus - Filzah Md Isa; Muhammed Abdullah Sharaf; Shaista Noor; Muhd Afiq Syazwan Ahmdon (Penerbit Universiti Kebangsaan Malaysia, 2024)
The correlation between curriculum design and a student’s knowledge and skills is pivotal. As the effective application of acquired knowledge and skills directly impacts individual work readiness and employability. Inherently, the employability of graduates has always been one of the main concerns among employers. In line with this issue, a qualitative study was conducted to investigate the graduates’ readiness for employment in Malaysia. This study delves into examining the universities’ curriculum design to understand the students’ view on the quality of the curriculum design for Master’s degrees in their respective Higher education Institution. The present study adopts the qualitative research strategy. A focus group discussion was conducted in English language in two universities - i.e., one public and one private. The reason to choose public and private universities is to get deeper exploration from both perspectives. From each of university 20-40 participants were involved in the focus group. During the focus group, the participants were led into a discussion on the relationship between curriculum design, work readiness and employability in Malaysian Higher Education. The audio-recorded focus groups were transcribed verbatim and analysed. The findings indicate the presence of effective modules and a moderate comprehensiveness of the Postgraduate program modules (Master), which influence the students’ knowledge and skills relevant to their jobs and readiness for employment. For the practical implications, universities need to add problem-based learning, internship and apprenticeship, field trips and site visit, technology integration and project-based learning modules to enhance their graduates’ employability and prepare them for any uncertainties.